Nilai Indeks Shine dan LAL antara Anemia Defisiensi Besi dengan Thalassemia di RSUD Dr. H. Abdul Moeloek - Syuhada Syuhada; Zulhafis Mandala; Astri Pinilih; Dwita Canggi Siregar (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Iron deficiency anemia and β minor thalassemia have the same morphological picture of hypochromic blood, therefore it needs to be distinguished from an examination. The diagnosis of β-thalassemia minor and iron deficiency anemia can be made by conducting a series of screening laboratory tests, ranging from the routine hematological examination, peripheral blood smear preparations, staining of peripheral blood smear preparations with supravital staining for reticulocyte counts and detection of HbH inclusion objects in erythrocytes, reserve status iron blood with a groove examination in stages until a sophisticated examination that is Hb electrophoresis and DNA examination. Objective: To find out the comparison of the shine & lal index between iron deficiency anemia patients and thalassemia patients in Dr. H. Abdul Moeloek Lampung Province. Method: This type of research is a comparative test. With the number of samples using a ratio of 1: 1 so that 45 people with iron deficiency anemia and 45 people with thalassemia found in Dr. H. Abdul Moeloek Lampung Province. Results: The Mann-Whitney test results showed a sig value of 0.029. Then H1 is accepted because of the value of sig <0.05. Conclusion: There is a significant difference in the value of the shine & lal index between iron deficiency anemia patients and thalassemia patients in Dr. H. Abdul Moeloek Lampung Province